Rethinking conceptual frameworks and models of health and natural environments. (March 2019) - Lawrence, Roderick John; Forbat, Julien; Zufferey, Joris
This article considers conceptual frameworks and models applied in research about the multiple relations between human contact with natural environments (specifically green public spaces), diverse kinds of human activities and uses of those spaces, and effects on physical and mental health. Conceptual frameworks are tools for thinking about such complex subjects. Conceptual models represent the multiple relations between key factors and variables. These models can be used to represent the mutual interactions between the core components of environmental conditions of specific green public spaces, the main kinds of human activities in those settings, and various impacts on health. A literature search showed that the authors of various conceptual models used a metaphor of pathways to represent relations between explanatory variables by linear cause–effect relations. Mutual interaction between key variables and feedback loops between different components of the model are rarely included. Hence, it is argued that these models do not represent the complexity of real world situations. The authors propose a systemic conceptual framework founded on core principles of human ecology. The proposed conceptual framework and model have been formulated during and after an EU 7th Framework project about the ''Positive Health Effects of the Natural Outdoor Environment in Typical Populations in Different Regions of Europe."